If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -18 = -7x + -21 + 9x + -6 Reorder the terms: -18 + 3x = -7x + -21 + 9x + -6 Reorder the terms: -18 + 3x = -21 + -6 + -7x + 9x Combine like terms: -21 + -6 = -27 -18 + 3x = -27 + -7x + 9x Combine like terms: -7x + 9x = 2x -18 + 3x = -27 + 2x Solving -18 + 3x = -27 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -18 + 3x + -2x = -27 + 2x + -2x Combine like terms: 3x + -2x = 1x -18 + 1x = -27 + 2x + -2x Combine like terms: 2x + -2x = 0 -18 + 1x = -27 + 0 -18 + 1x = -27 Add '18' to each side of the equation. -18 + 18 + 1x = -27 + 18 Combine like terms: -18 + 18 = 0 0 + 1x = -27 + 18 1x = -27 + 18 Combine like terms: -27 + 18 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| 4(2x+5)=10x+19-2x+1 | | x+5-4x+9= | | 8x+3=4x+27 | | 9x+3=7x+6 | | 12-8=4 | | 3x+12x-3=3(5x+5) | | 93/x=6 | | 43=8r-5 | | 0=-9(0) | | (6z+2)+(18)=14z | | 7a+12a=72 | | 1-e^3k=5 | | X-485.99=853.5 | | 5x+2(x-4)=8x+2 | | 3(36)-4= | | 3x/20-9/4=6 | | -5+z=-28 | | -63=-9(8) | | 7(x+3)+9=3(x-4)+6 | | 1-e^3=5 | | 89.48+x=125.87 | | 2x-2=70-10x | | 6+5=-29 | | 4x+8+4=8 | | -x(x)-2x+3=3 | | m-10/3-5m-10/4=1 | | z+1=9z-7 | | 4(30)-9= | | 27(2b-1/3) | | x/4=x/2-8 | | 16y+2y-(-20)=2 | | 57.45+x=94.92 |